The relationship between depressive symptoms, health service consumption, and prognosis after acute myocardial infarction: a prospective cohort study - Gnam William H; Kurdyak Paul A; Goering Paula; Chong Alice; Alter David A (BMC, 2008)
Abstract Background The use of cardiovascular health services is greater among patients with depressive symptoms than among patients without. However, the extent to which such associations between depressive symptoms and health service utilization are attributable to variations in comorbidity and prognostic disease severity is unknown. This paper explores the relationship between depressive symptoms, health service cardiovascular consumption, and prognosis following acute myocardial infarction (AMI). Methods The study design was a prospective cohort study with follow-up telephone interviews of 1,941 patients 30 days following AMI discharged from 53 hospitals across Ontario, Canada between December 1999 and February, 2003. Outcome measures were post discharge use of cardiac and non-cardiac health care services. The service utilization outcomes were adjusted for age, sex, income, comorbidity, two validated measures of prognosis (cardiac functional capacity and risk adjustment severity index), cardiac procedures (CABG or PTCA) and drugs prescribed at discharge. Results Depressive symptoms were associated with a 24% (Adjusted RR:1.24; 95% CI:1.19-1.30, P < 0.001), 9% (Adjusted RR:1.09; 95% CI:1.02-1.16, P = 0.007) and 43% (Adjusted RR: 1.43; 95% CI:1.34-1.52, P < 0.001) increase in total, cardiac, and non-cardiac hospitalization days post-AMI respectively, after adjusting for baseline patient and hospital characteristics. Depressive-associated increases in cardiac health service consumption were significantly more pronounced among patients of lower than higher cardiac risk severity. Depressive symptoms were not associated with increased mortality after adjusting for baseline patient characteristics. Conclusion Depressive symptoms are associated with significantly higher cardiac and non-cardiac health service consumption following AMI despite adjustments for comorbidity and prognostic severity. The disproportionately higher cardiac health service consumption among lower-risk AMI depressive patients may suggest that health seeking behaviors are mediated by psychosocial factors more so than by objective measures of cardiovascular risk or necessity.